SURVIVAL LONGEVITY OF Clonorchis sinensis METACERCARIAE COLLECTED IN RAY - FINNED FISH (Toxobramis houdemeri) IN VITRO CONDITION (Vietnam Journal of Agriculture and Environment, 2023)
Clonorchis sinensis is a biological carcinogen inducing human cholangiocarcinoma (CCA). Clonorchiasis is one of the important endemic infectious diseases in Vietnam. The present study investigated the survival longevity of C. sinensis metacercariae in various in vitro conditions to find the best way of inactivating metacercariae in fish muscle. The fish (n=910; 6.74 - 9.85 cm in length, and body weight 4.52 - 7.42 g/fish) were randomly sampled from Thac Ba reservoir, Yen Bai province. A total of 2358 C. sinensis metacercariae were detached from soaked fish individuals with different solutions of Lemon juice, Vinegar, Alcohol 55%, and NaCl 10% at different immersion times (1, 6, 12, 24, 48, 72 hours) to evaluate the inactivated rate of metacercariae. The results showed that the metacercariae did not die after 1 and 6 hours in 4 different solutions. However, a proportion of C. sinensis metacercariae (40%) immersed in Alcohol 55% became inactivated after 12 hours. The mortality rate of C. sinensis metacercariae in the Alcohol was higher than in Vinegar, Lemon juice, and NaCl during all the time of the experiment. These data suggest that Alcohol 55% are effective for inactivating metacercariae of C. sinensis after 60 hours.